2008
DOI: 10.1007/s12185-008-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of adult acute leukemia with 11q23 abnormalities in Japan: a co-operative multicenter study

Abstract: To clarify the clinical features of adult patients with acute leukemia (AL) with 11q23 abnormalities, we performed a retrospective analysis of data from 58 adult Japanese patients: 51 with acute myeloid leukemia (AML), and 7 with acute lymphoblastic leukemia (ALL). The incidences according to fusion partners in AML were: t(9;11), 31.3%; t(11;19), 27.4%; t(6;11), 21.5%. The incidence of patients with t(11;19) was higher than those in the US and Europe, and the incidence of t(4;11) was lower than that in childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
10
1
1
Order By: Relevance
“…However, t(11;19) was also identified as an independent adverse prognostic feature in adult AML, a finding that is consistent with the results reported in the majority of other such studies 16, 17, 25 but that conflicts with the findings of a recent study by the Medical Research Council. 4 …”
Section: Discussionsupporting
confidence: 83%
“…However, t(11;19) was also identified as an independent adverse prognostic feature in adult AML, a finding that is consistent with the results reported in the majority of other such studies 16, 17, 25 but that conflicts with the findings of a recent study by the Medical Research Council. 4 …”
Section: Discussionsupporting
confidence: 83%
“…The frequency of MLL gene rearrangement in Japanese adult t-AML was (27.4%) [16] and higher than was reported to be about 5–10% in Caucasian populations [17,18], with different frequency from different European countries from 5 to 15% [19,20,21]. This difference may be due in part to the lack of attention to t-MDS, which focused on primary MDS and t-AML, also due to different numbers of patients involved in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…30 In a previous study in a population of adult Japanese patients, the 1-year EFS was 22.2% and the 2-year OS was 33.7%, indicating a similarly poor prognosis to that in the CALGB study. 43 The prognosis of children with AML with t(6;11) (p27;q23) is also very poor. The results of an international retrospective study performed in 2009 indicated a 5-year OS and EFS of patients with t(6;11) (p27;q23) of 22% and 11%, respectively.…”
Section: ) A4) Aml With T(6;11) (P27;q23) (Mll-af6)mentioning
confidence: 99%